KEANEKARAGAMAN IKAN DI SUNGAI SULUP KECAMATAN RIMBO PENGADANG KABUPATEN LEBONG PROVINSI BENGKULU - Pariyanto Pariyanto; Endang Sulaiman; Rukiah Lubis (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the diversity of fish species in Sulup River, Rimbo Pengadang District, Lebong Regency, Bengkulu. The Research was conducted from in April-May 2020. The method used in this study is a direct survey method. The sampling method used is purposive sampling by dividing the research station into 3 stations based on river conditions. The types of fish found in the Sulup River Rimbo Pangadang District Lebong Regency Bengkulu Province were found as many as 4 orders, 4 families with 8 species namely species Mystus singaringan, Angullia marmorata, Osteochilus vittatus, Hampala macrolepidota, Barbonymus gonionotus, Schismatorhynchos heterorhynchos, Rasbora argyrotaenia and Mastacembelus armatus. The ecological conditions in the Sulup river have a temperature of 230C, a depth of 1.5 m, 45 cm river clarity, water pH 7, flow velocity 0.66 m/sec. Sulup River has a diversity index of 0.840, so the diversity index is low.